Increased plasma soluble CD40 ligand concentrations in systemic sclerosis and association with pulmonary arterial hypertension and digital ulcers. Issue 3 (11th February 2005) - Allanore, Y; Borderie, D; Meune, C; Lemaréchal, H; Weber, S; Ekindjian, O G; Kahan, A
Abstract : Background: Increased expression of CD40L has been reported on activated CD4+ T lymphocytes in systemic sclerosis. CD40L can be expressed in soluble form (sCD40L). Objective: To compare sCD40L concentrations in patients with systemic sclerosis and healthy controls. Methods: Quantitative sandwich ELISA was used to measure plasma sCD40L in systemic sclerosis (n = 50) and matched healthy controls (n = 20). Patients with systemic sclerosis had limited cutaneous disease (29), digital ulcers (14), pulmonary arterial hypertension (PAH) (10), pulmonary fibrosis on CT (23), positive anti-Scl70 (14), and anti-centromere antibodies (10). Calcium channel blockers were discontinued 72 hours before measurements. Results: Median (range) sCD40L concentration (pg/ml) was higher in systemic sclerosis than in controls (495 (10 to 7720) v 79 (50 to 118); p = 0.003), in limited cutaneous disease v diffuse disease (620 (20 to 7720) v 250 (10 to 2690); p = 0.005), in patients with digital ulcers v those without (1430 (36 to 7720) v 370 (10 to 2320); p = 0.002), and in those with PAH v those without (995 (15 to 3850) v 400 (10 to 7720); p = 0.048). sCD40L correlated with pulmonary arterial pressure estimated by Doppler echocardiography ( r = 0.41; p = 0.005). Conclusions: The soluble form of CD40L is increased in plasma in systemic sclerosis and may be associated with vascular complications of the disease.